Evaluation Of Industrial Workplace Exposure To Metal Fumes Using Toenail As Bio-Indicator - Zainal Bakri, Siti Farhana; Hariri, Azian; Ismail, Marzuki; Muhamad Damanhuri, Amir Abdullah (Penerbit UTHM, 2019)
The toxic gaseous generated from welding process contained heavy metals that induce various cancers and diseases. Exposure to this toxic fume is associated with the occurrence of lung cancer and worker that exposed to this situation is considered as a high-risk group. This study aims to investigate the amounts of heavy metals concentration in the breathing zone and toenail samples of 36 individuals from automotive related industries in Malaysia that were classified as an exposed group (welders) and non-exposed group (office workers) by cross-sectional research design. Personal air sample and mixed cellulose ester (MCE) filters were used to collect the welding fumes while toenail samples from all 10 toes of each subject for biomonitoring. Collected samples were digested, and analyzed to evaluate the levels of heavy metals by inductively coupled plasma mass spectrometry (ICP-MS). Eleven heavy metals (Al, Cr, Mn, Fe, Co, Ni, Zn, Cu, As, Ag, and Pb) were measured in all samples; and results showed that the concentrations of Cr, Zn, As, Ag and Pb were significantly difference (P ≤ 0.05) for exposed and non-exposed groups. Furthermore, the metal fume exposure generated from different welding types in these three plant shows a similar exposure to the welders. Thus, more attention need to be considered to the working conditions of the exposed group, specifically on providing proper ventilation at the workplace as well as to provide a suitable protective personal devices.